PEMBAGIAN WARIS PADA KOMUNITAS TAMIL MUSLIM DI KOTA MEDAN - MUMTAZHA AMIN (PREMISE LAW JURNAL, 2016)
Tamil Moslem community is a group of Indian Tamils who are Moslems. They have kinship, wedlock, and inheritance which are influenced by their own original culture. Since they become Moslems, they have to comply with the Islamic law. However, it seems that acculturation plays an important role in creating law. The problems of the research were as follows: how about the inheritance system, how about its influence, and what factors which impede the settlement of dispute in inheritance in it its distribution in the Tamil Moslem community in Medan. The research used normative empirical method. The data were gathered by performing sociological research or a judicial research by optimizing judicial normative materials and primary data which were obtained from the informants who were related to the heirs of the inheritance case. The gathered data were analyzed by using qualitatively and the conclusion was drawn deductively and presented descriptively. The result of the research shows that the inheritance system used by the Tamil Moslem community in Medan is male inheritance system in which the oldest man in the family has the right to lead, control, and organize the inheritance. The Islamic inheritance law has its influence in the Tamil Moslems on determining the classification of heirs and the portion between male heirs and female heirs. This influence is caused by religious and educational factors which influence someone in adopting a certain law. The inhibiting factors in settling the dispute in inheritance in Tamil Moslem community in Medan are internal and external factors. Internal factors include consanguinity system in the Tamil Moslem community which tends to be secluded, law which is determined by the heirs in distributing inheritance is not consistent, and dominant control by the oldest brother. External factors include the influence of limited social environment and lack of socialization about the Islamic law. Keywords: Islamic Inheritance Law, Distribution of Inheritance, Tamil MoslemCommunity, Choice of Law